Carbachol injection into the medial preoptic area induces natriuresis, kaliuresis and antidiuresis in rats - Luca Junior, Laurival Antonio de [UNESP]; Saad, Wilson Abrão [UNESP]; de Arruda Camargo, Luiz Antonio [UNESP]; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP]; Saad, William Abrão [UNESP] (Elsevier, 1989)
The microinjection of carbachol into the medial preoptic area (MPO) of the rat induced natriuresis, kaliuresis and anti-diuresis in a dose-related manner. Atropine blocked all responses to carbachol. Hexamethonium impaired the dose-response effect of carbachol on kaliuresis, but had no effect on natriuresis and enhanced the antidiuretic effect of carbachol. Nicotine alone had no effects, but pre-treatment with nicotine enhanced the responses to carbachol. These data show that activity of the muscarinic receptors of the MPO increases renal electrolyte and reduces water excretion. They also suggest that nicotinic receptors have an inhibitory effect on water excretion. Nicotine could act through mechanisms unrelated to nicotinic receptors to enhance the effect of the carbachol. © 1989.
Keywords: Carbachol; Medial preoptic area; Nicotine; Potassium excretion; Sodium excretion; Water excretion; atropine; carbachol; hexamethonium; nicotine; nicotinic receptor; animal cell; animal experiment; female; histology; intracerebral drug administration; medial preoptic area; nonhuman; potassium excretion; priority journal; rat; sodium excretion; Animal; Atropine; Dose-Response Relationship, Drug; Hexamethonium Compounds; Male; Potassium; Preoptic Area; Rats; Sodium; Support, Non-U.S. Gov't; Water